2000
DOI: 10.1143/jjap.39.l1039
|View full text |Cite
|
Sign up to set email alerts
|

Photonic Band Gap in Anodic Porous Alumina with Extremely High Aspect Ratio Formed in Phosphoric Acid Solution

Abstract: Two-dimensional (2D) photonic crystals were fabricated using anodic porous alumina with a highly ordered air-hole array of triangular lattice with a high aspect ratio of over 200. The transmission properties of the obtained ordered air-hole array in the alumina matrix exhibited a stop band in the spectrum which corresponds to the band gap in 2D photonic crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 10 publications
2
70
0
Order By: Relevance
“…The uniform pores orderly aligned on the n-InP͑001͒ substrates and constructed a triangular lattice. These features are very similar to the Al 2 O 3 porous structures reported by Masuda et al 16 We have previously reported that the InP nanowalls were standing vertically to a ͑001͒ plane, keeping good uniformity over 19 m.…”
supporting
confidence: 87%
“…The uniform pores orderly aligned on the n-InP͑001͒ substrates and constructed a triangular lattice. These features are very similar to the Al 2 O 3 porous structures reported by Masuda et al 16 We have previously reported that the InP nanowalls were standing vertically to a ͑001͒ plane, keeping good uniformity over 19 m.…”
supporting
confidence: 87%
“…According to the growth model of AAO proposed by Masuda et al [9,10], morphology and arrangement of pores in the initial part of porous AAO are irregular. Following the formation of AAO, the morphology and the arrangement of pores in porous AAO are changed more and more regular because of the mechanical stress, which is associated with the volume expansion during the formation of AAO.…”
Section: Resultsmentioning
confidence: 99%
“…Anodic aluminum oxide (AAO) is a kind of self-organizing material with nanopore arrays [6][7][8][9][10][11]. The ideal model of AAO can be schematically represented as figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their low absorption coefficient, excellent thermal stability and easy handling, porous alumina structures could be potential materials for photonic crystals. However, since a perfect arrangement of porous alumina channels is required for 2-D PCs, only few studies on porous alumina photonic crystals exist [5][6][7]. To fabricate monodomain porous alumina structures, a method to pre-pattern the surface of aluminum before conventional anodization is a prerequisite.…”
Section: Introductionmentioning
confidence: 99%